The Importance and Need for the Development of Technical Thinking of Students in the Field of Circuit Training From Physics - Bakhodirovich, Umirov Habibullo (European Journal of Life Safety and Stability (2660-9630), 2022)
This article covers the importance and necessity of developing the technical thinking of students in their exercise of circular from physics. The author, relying on pedagogical data and physical sources, made clear the problem on the basis of existing scientific and historical literature. In his lectures from physics to the circle, he made a comparative analysis of the existing specific approaches and theories on the importance and need to develop the technical thinking of students.